2010
DOI: 10.1016/j.pepi.2010.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the simultaneous shock magnetization and demagnetization of rocks

Abstract: International audienceIn the natural case of an hypervelocity impact on a planetary or asteroidal surface, two competing phenomena occur: partial or complete shock demagnetization of pre-existing remanence and acquisition of shock remanent magnetization (SRM). In this paper, to better understand the effects of shock on the magnetic history of rocks, we simulate this natural case through laser shock experiments in controlled magnetic field. As previously shown, SRM is strictly proportional to the ambient field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…The surface morphology of the Terra has been investigated in recent past. Using two independent techniques, fault scarp width and crater elongation methods, Golombek et al (1996) concluded that the Tempe Terra region has stretched about 21 km in the northwest-southeast direction, and majority of the extension took place as a result of early Tharsis faulting in Late Noachian to Early Hesperian (Tanaka et al, 1991). With its complex Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface morphology of the Terra has been investigated in recent past. Using two independent techniques, fault scarp width and crater elongation methods, Golombek et al (1996) concluded that the Tempe Terra region has stretched about 21 km in the northwest-southeast direction, and majority of the extension took place as a result of early Tharsis faulting in Late Noachian to Early Hesperian (Tanaka et al, 1991). With its complex Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The area is cut to be similar to the areas of the other QCDs in this figure for presentation purposes. pattern of graben and faults with rift-related volcanism (Hauber and Kronberg, 2001), and the regional strain of 2-3%, the Tempe Terra is the most highly strained province around Tharsis (Golombek et al, 1996). Most of the extension was accommodated during two main phases of extension that occurred throughout Tharsis, from Middle/Late Noachian to Early Hesperian and from Late Hesperian to Early Amazonian.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the high-(noncollective) scattering regime the total inelastic portion of the dynamic structure factor is constructed using equation (5) sufficiently small that we substitute ( ) for ( ) without introducing appreciable systematic error, allowing to be factored out of the integrand in equation (4). Similarly, the FWHM of ( ) (which, in the impulse approximation, is directly related to the width of the momentum distribution of the electronic ground state) is small compared to our required energy resolution, such that we can define a Compton-shifted energy variable and re-express (4) in approximate form:…”
Section: Iib Photon-electron Interactions and Numerical Modelingmentioning
confidence: 99%
“…2(c). We note that ED-XRD has a long history in laboratory and synchrotron XRD studies, and plays an important role 4 in high-pressure diamond anvil cell research where the limited angular access to the sample space substantially complicates AD-XRD. [36][37][38][39][40] There is then an obvious commonality with experiments at large-scale laser facilities; angular access at such facilities is strongly constrained by the beam paths of the laser light itself.…”
Section: Introductionmentioning
confidence: 99%